2018
DOI: 10.1111/vru.12628
|View full text |Cite
|
Sign up to set email alerts
|

Mineralization can be an incidental ultrasonographic finding in equine tendons and ligaments

Abstract: Tendon/ligament mineralization is recognized in horses but information regarding its clinical significance is limited. The aims of this observational study were to report the structures most commonly affected by ultrasonographically detectable mineralization and, for these, determine frequency of diagnosis and key clinical features. Cases presented at our hospital in April 1999-April 2013 and September 2014-November 2015 were included: a total of 27 horses (22 retrospective, five prospective). Mineralizations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 35 publications
2
17
0
1
Order By: Relevance
“…In this study, Etienne O'Brien and Roger Smith from the Royal Veterinary College, UK, reported the structures most commonly affected by ultrasonographically detectable mineralisation .…”
Section: Tendon and Ligament Mineralisationmentioning
confidence: 99%
“…In this study, Etienne O'Brien and Roger Smith from the Royal Veterinary College, UK, reported the structures most commonly affected by ultrasonographically detectable mineralisation .…”
Section: Tendon and Ligament Mineralisationmentioning
confidence: 99%
“…Dystrophic mineralisation of ligaments and tendons has been reported in many different anatomical locations in the horse (Garvican et al 2016; O’Brien and Smith 2018; Kadic et al 2019). Mineralisation may occur following abnormalities of calcium metabolism, or as a response to injury, degeneration, or inflammation of a ligament (Kumar et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Mineralisation may occur following abnormalities of calcium metabolism, or as a response to injury, degeneration, or inflammation of a ligament (Kumar et al 2017). Dystrophic calcification is common in the tendons and ligaments of horses (Smith et al 2008; O’Brien and Smith 2018) compared to metastatic calcification. In many cases, ectopic mineralisation of ligamentous structures in the horse is considered an incidental finding, whereas in others clinical signs and diagnostic investigations suggest significance of these abnormalities (O’Brien and Smith 2018; Kadic et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The process of tendon healing is slow; this poor healing ability happens due to its hypo-vascularity in tandem with hypo-cellularity. The scar formation and ectopic mineralization after tendon injury can induce rupture in the tendon of predisposed horse and happen through increased expression of collagen type III (COL3) that has smaller fibers and fewer crosslink compared to collagen type I (COL1) leading to inferior mechanical properties [10, 11]. The current treatment options result in pain relief or replacement of the injured tissue that remained as a clinical challenge to achieve a functional tissue.…”
Section: Introductionmentioning
confidence: 99%